Effectiveness of Red Onion Extract (Allium Cepa) on the Elongation of Papillae and Neutrophil Cell in the Gastroesophageal Junction (GEJ) of Sprague Dawley Strain Rats Gastroesophageal Reflux Disease (GERD) Model - Blandina, Maria Bernadetta Nadya; ., Vetinly; Djuartina, Tena; Tenggara, Riki; Budianto, Iskandar R. (The Indonesian Society for Digestive Endoscopy, 2025)
Background: Gastroesophageal acid reflux disease (GERD) is a disorder caused by the reflux of stomach acid when the lower esophageal sphincter (LES) relaxes with a prevalence of around 1.03 billion worldwide. One of the supporting examinations carried out to diagnose GERD is a histopathological examination. This study aims to determine the effect of red onion extract on the papillae elongation and neutrophil cells of the gastroesophageal junction in Sprague Dawley rats. Methods: This experimental study was conducted on Sprague Dawley rats induced with 1 mL of HCl + 1 mL of ascorbic acid, administered into the gastric cardia of the rats, mixed with 1 mL of sodium thiocyanate (NaSCN) and 1.5 mL of sodium nitrite (NaNO₃) to develop a GERD model. The rats were then divided into ten groups with different treatments, including red onion extract (250, 500, 750 mg/kgBW) and PPI (pantoprazole). Results: It was stated that there was a significant relationship between the effect of red onions and changes in papillae elongation in rats induced by GERD (P-value 0.05). The neutrophil cells showed no significance on the impact of red onion (p-value 0,05). Nor are the papillae elongation and the neutrophil cell changes dose-dependent.Conclusion: A significant reduction in the histopathological appearance of papillae elongation was seen in the majority of the population. However, no significant results were found for the different doses of shallot extract.Keywords: Gastroesophageal acid reflux disease, allium cepa, papillae elongation, red onion extract, neutrophil cells